BIOACCUMULATION OF HEAVY METALS AND HEALTH RISK ASSESSMENT AFTER THE CONSUMPTION OF SOME VEGETABLES GROWN ALONG RIVERS JAKARA AND GETSI IN ALBINO RATS (FUDMA JOURNAL OF SCIENCES, 2022)
Cabbage and lettuce were collected from three locations each along the irrigation farms of Rivers Jakara and Getsi. Domestic and industrial waste are freely discharge into these rivers.   Thirty Nine Albino Rats were divided into Thirteen (13) groups where Animals in groups 1-12 were fed with diet containing 10% cabbage or lettuce. The 13th group were fed with normal diet. After 90 days, the Animals were sacrificed, blood and organs were collected. Fe had the highest level in the blood and significantly different from the control in all the groups. The level of other essential heavy metals is in the following order of decreasing concentration, Fe> Zn > Cu > Cr > Mn > Co while Pb has the highest concentration and in the following order of decreasing concentration Pb > As > Cd > Ni > Hg. A significant decrease in weight of the heart, kidney and pancreas was observed and a significance difference in the organ/body weight coefficient was observed in the Liver (group 3, 4 and 11) Kidney (group 5, 6 and 7) and Pancreas (group 1, 3 and 9). The bioaccumulation index (BAI) shows that eight (8), Seven (7) and Six (6) of the elements analyzed accumulates in the Liver and the Pancreas, Kidney and Heart respectively. Liver accumulated more Cadmium, Lead and Nickel while Pancreas accumulated Nickel, Manganese and Cobalt. Consumption of these vegetables led to reduction in organ weight, increase blood levels and bioaccumulation of some heavy metals in vital organs of albino rats
Keywords: Heavy Metals, Organ/Body weight Coefficient, Bioaccumulation Index, Albino Rats